Constant-Factor Approximation Algorithms for a Series of Combinatorial Routing Problems Based on the Reduction to the Asymmetric Traveling Salesman Problem - Khachay, M. Yu; Neznakhina, E. D.; Ryzhenko, K. V. (Proceedings of the Steklov Institute of Mathematics, 2022)
For the first time, algorithms with constant performance guarantees are substantiated for a series of asymmetric routing problems of combinatorial optimization: the Steiner cycle problem (SCP), the generalized traveling salesman problem (GTSP), the capacitated vehicle routing problem with unsplittable customer demands (CVRP-UCD), and the prize collecting traveling salesman problem (PCTSP). The presented results are united by the property that they all rely on polynomial cost-preserving reduction to appropriate instances of the asymmetric traveling salesman problem (ATSP) and on the 22 𝜀 -approximation algorithm for this classical problem proposed by O. Svensson and V. Traub in 2019.